Pengaruh Penambahan Jumlah User Dan Jarak Pada Komunikasi D2D Unicast Dengan SimuLTE - Rifki Rifki; Yusnita Rahayu; Antonio Virdis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The increased number of users and distance of communication, it caused the network quality decreased in the Device-To-Device (D2D) communication system. In this paper, simulation on D2D unicast by using SimuLTE software is presented. This is in order to evaluate the effect of the number of users and the distance to the quality of D2D network in terms of Channel Quality Indicator (CQI) and Throughput Media Access Control (MAC) on downlink and uplink condition. From the simulation results, the distance which is greater than 50 meters resulted in the decrease of Channel Quality Indicator (CQI). However, Throughput Media Access Control (MAC) on downlink is better than the uplink condition. The increased number of users reduces the MAC throughput in both uplink and downlink conditions. Thus, as a conclusion, the quality of the D2D network has better performance in short distance rather than long distance with a few number of users.Keyword : D2D Communication, SimuLTE, CQI, Throughput MAC